A long-term prospective observational study in 31 patients with hemicrania continua. (22nd January 2019) - Prakash, Sanjay; Rathore, Chaturbhuj; Rana, Kaushik; Joshi, Hemant; Patel, Jay; Rawat, Kalu Singh
Introduction: Till date, there is no prospective study in patients with hemicrania continua (HC). Methods: Patients fulfilling the international classification of headache disorders criteria for HC were evaluated prospectively. All patients were subjected to a detailed clinical interview, based on a structured questionnaire. Before starting indomethacin, all patients were instructed to fill a headache diary for at least 5 days. Gradual tapering of indomethacin was done at regular intervals. Results: We enrolled 41 patients over 4.5 years, 31 of whom met the criteria after confirming the indomethacin response. The mean age was 41 years, and 55% were female. The mean duration of headache was 43.6 months. All patients had continuous strictly unilateral pain with episodic exacerbations. At least one cranial autonomic feature was noted in 81% of patients. Twenty-five patients (81%) felt a sense of restlessness during exacerbations. The mean follow-up was 2.5 years. Three-fourths of patients noted a reduction in indomethacin dose after an average 2.5 of years follow-up. The mean reduction of the dose in the follow-up was statistically significant (172 mg vs. 110 mg, p < 0.001). All patients missed the drug for various reasons over the observation period. The headache reappeared within 48 h in 97% of patients. Conclusion: Misdiagnosis of HC is still very common. Patients may not volunteer about the background pain and will focus only on the exacerbations. HC rarely remits, but indomethacin requirements may decrease over time. Skipping of the effective drug leads to the immediate reappearance of pain.